"Employment until the end of the world": Exploring the role of manipulation in a Mozambican land deal. (February 2019) - Arnall, Alex
Highlights: Farmer manipulation is a pervasive influence in large scale land acquisitions. Manipulation includes deception, pressure to acquiesce and playing on emotions. Farmers were manipulated into leasing land, decisions that many later regretted. The livelihoods of the smallest-scale farmers were undermined as a result. A wider set of influences should be considered in land deals than coercion alone. Abstract: In recent years, there has been considerable controversy over the poverty and livelihood impacts of large-scale land acquisitions (LSLAs) on small-scale farmers in sub-Saharan Africa. However, while much of the concern over LSLAs has stemmed from the phenomenon of coercive expulsion of farmers from their lands, far less attention has been paid to the mechanism of manipulation, which is arguably a subtler and more pervasive form of influence over smallholders when they are incorporated into major land deals. This article addresses this theoretical and empirical gap through a case study of a LSLA implemented by an international paper and pulp company for the development of an extensive eucalyptus plantation in central Mozambique. The findings highlight the roles of three forms of manipulative influence – namely deception, pressure to acquiesce and playing upon people's emotions – that were evident during company-smallholder negotiations and the impacts that these had on farmers' livelihoods. The article concludes that, in the study of LSLAs, a much wider range of influences should be taken into consideration during the implementation of land deals than is currently the case. This is particularly important when external investors seek to develop new markets for land in which small-scale landholders can engage on a supposedly voluntary basis in search of jobs and income.